Active Range of Motion Exercises and Muscle Strength in Post-Stroke Patients: A Study at Ketapang Health Center - Anugrah, Tri Yayan; Anita, Fitri; Sari, Septi Kurnia (Inspirasi Foundation, 2026)
Introduction: Stroke is a condition that occurs when the blood supply to the brain is disrupted or reduced due to a blockage (ischemic stroke) or rupture of a blood vessel (hemorrhagic stroke). Without blood supply, the brain will not receive oxygen and nutrients, causing cells in some areas of the brain to die. This condition causes the body parts controlled by the damaged brain area to not function properly. Objective: The effect of active ROM on muscle strength of stroke patients in the working area of ​​Ketapang Health Center, Ketapang District, South Lampung Regency in 2025. Method: This type of research is quantitative research. The research design used in this study is a Two-group design. This research was conducted in January 2025 in the working area of the Ketapang Health Center, South Lampung Regency. The population in this study was 19 people. The sample in this study was 18 people who were divided into 2 groups, namely 9 people in the Active ROM group and 9 people in the passive ROM group. Result: The results of the study showed that there was an increase in muscle strength values in respondents who were given active ROM actions, namely 0.56 points. Meanwhile, respondents who were not given ROM treatment experienced a decrease in muscle strength by 0.11 points. The results of the statistical test obtained a ρ value of 0.041, <0.05. Conclusion: There is an effect of active ROM on muscle strength in stroke patients in the Ketapang Health Center work area, Ketapang District, South Lampung Regency in 2025.